ACTIVITIES OF FOREIGN LANGUAGE TEACHERS AS A CURATOR IN THE EDUCATIONAL PROCESS OF THE HIGHER EDUCATIONAL PROCESS - Komilova Gulnoz Uzokovna (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
This article deals with issues related to the curatorial activities of teachers of foreign languages of the university.